Influence of metal particles shape on direct current voltage electric properties of nanofluids - Fahmi, Daniar; Akbar, Muhammad Fadlan; Yulistya Negara, I Made; Hernanda, I Gusti Ngurah Satriyadi; Asfani, Dimas Anton; Zaidan, Risyad Alauddin; Fadhilah, Arkan (Institute of Advanced Engineering and Science, 2025)
It is widely recognized that the application of nanoparticles has the potential to improve the dielectric properties of transformer oil. Nevertheless, there is a scarcity of studies that have utilized pure nanofluids, and in practical applications, it is inevitable for transformer oil to become contaminated. Therefore, this study conducted tests to investigate how the shape and size of metal contaminants impact the dielectric performance of Fe3O4 nanofluids. The findings from the levitation voltage test indicate that as the size and diameter of the particle increase, the levitation voltage value measured also increases, and conversely. Moreover, a higher concentration of nanoparticles leads to a higher measured levitation voltage value. On the other hand, the breakdown voltage test results demonstrate that larger and sharper particles result in lower measured breakdown voltage values, and vice versa. The simulation outcomes regarding electric field distribution reveal that larger and sharper particles correspond to higher measured electric field values, while the opposite is true for smaller and less sharp particles.